Analisis Ketepatan Dan Kelancaran Berbicara Siswa Dengan Metode Tanya Jawab - Anjar Zuliasih, Dwi; Septiani, Rizki Maulida; Naela, Fatkhatun; Rizqina, Ariny (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Speaking skills are one of the essential language competencies in learning Indonesian, particularly in helping students express ideas accurately and fluently. However, various national studies indicate that many students still face difficulties in speaking, both in terms of accuracy and fluency. This study aims to analyze students’ speaking performance in depth, focusing specifically on accuracy and fluency within classroom question-and-answer activities. A descriptive qualitative approach was employed, as the research emphasizes portraying students’ oral performance naturally without any experimental manipulation. Data were collected through direct observation of classroom interactions, audio and video recordings of students’ utterances, interviews with students and teachers, and documentation of instructional materials. Data analysis consisted of data reduction, data display, and conclusion drawing, while data validity was ensured through technique triangulation, source triangulation, and member checking. The findings indicate that students’ speaking abilities are developing but remain suboptimal. In terms of accuracy, some students were able to use context-appropriate vocabulary and form simple grammatical structures correctly, yet errors in diction, ineffective sentence construction, and unclear pronunciation were still commonly found. Regarding fluency, students tended to exhibit long pauses, word repetitions, and hesitation when giving spontaneous responses. Psychological factors such as anxiety and low self-confidence significantly influenced their speaking performance. These findings highlight that the question-and-answer method effectively stimulates spontaneous responses but requires structured practice to improve both accuracy and fluency more optimally.